The $$D_{s1}(2460) → D_s π ^+ π ^- $$ D s 1 ( 2460 ) → D s π + π - decay from a $$D_{s1}$$ D s 1 molecular perspective - Luis Roca; Jorgivan Morais Dias; Eulogio Oset (European Physical Journal C: Particles and Fields)
Abstract We conduct a theoretical study of the $$ D_{s1}(2460) → D_s π ^+ π ^- $$ D s 1 ( 2460 ) → D s π + π - decay from the perspective that the $$D_{s1}$$ D s 1 is a molecular state, built mostly from the $$D^* K$$ D ∗ K and $$D_s^* η $$ D s ∗ η components. The $$D^*$$ D ∗ and $$D_s^*$$ D s ∗ mesons are allowed to decay into two pseudoscalars, with one of them merging with the other pseudoscalar that forms the $$D_{s1}$$ D s 1 state, ultimately leading to the $$π ^+ π ^- D_s$$ π + π - D s final state. This results in a triangle diagram mechanism where all theoretical ingredients are well-known, leading to a free parameter framework. We evaluate the mass distributions of particle pairs and find good agreement with the experimental distributions of a recent LHCb experiment, providing strong support to the molecular picture of the $$D_{s1}(2460)$$ D s 1 ( 2460 ) state. We also discuss the role played by the scalar mesons $$f_0(500)$$ f 0 ( 500 ) and $$f_0(980)$$ f 0 ( 980 ) , at odds with the interpretation of the experimental analysis.